Expression, purification and structural analysis of functional GABA transporter 1 using the baculovirus expression system - Hu, Jing; Weise, Chris; Böttcher, Christoph; Fan, Hua; Yin, Jian (Beilstein Journal of Organic Chemistry, 2017)
The γ-aminobutyric acid (GABA) transporter 1 (GAT1) belongs to a family of Na+ and Cl−-coupled transport proteins and possesses 12 putative transmembrane domains. To perform structural analyses of the GAT1 protein, the GAT1/green fluorescent protein (GFP) fusion protein was functionally expressed in insect Sf9 cells by the BAC-TO-BAC® baculovirus expression system. A two-step procedure to purify the GAT1/GFP fusion protein from insect Sf9 cells has been established and involves immunoaffinity chromatography using self-prepared anti-GFP antibodies and size-exclusion fast protein liquid chromatography (SE-FPLC). A yield of 200–300 μg of the GAT1/GFP protein could be purified from 400–600 mL of infected Sf9 cells. The purified protein was analyzed by transmission electron microscopy (TEM), which revealed that the GAT1/GFP fusion protein was isolated in its monomeric form.
Keywords: baculovirus expression system; chromatography; γ-aminobutyric acid (GABA); GABA transporter 1 (GAT1)

(untitled) - Kanner, B. I. (J. Membr. Biol., 2006)

(untitled) - Nelson, N. (J. Neurochem., 1998)

(untitled) - Scimemi, A. (Front. Cell. Neurosci., 2014)

(untitled) - Liu, Q. R.; Lopez-Corcuera, B.; Mandiyan, S.; Nelson, H.; Nelson, N. (J. Biol. Chem., 1993)

(untitled) - Borden, L. A.; Smith, K. E.; Hartig, P. R.; Branchek, T. A.; Weinshank, R. L. (J. Biol. Chem., 1992)

(untitled) - Jursky, F.; Tamura, S.; Tamura, A.; Mandiyan, S.; Nelson, H.; Nelson, N. (J. Exp. Biol., 1994)

(untitled) - Borden, L. A. (Neurochem. Int., 1996)

(untitled) - Conti, F.; Minelli, A.; Melone, M. (Brain Res. Rev., 2004)

(untitled) - Guastella, J.; Nelson, N.; Nelson, H.; Czyzyk, L.; Keynan, S.; Miedel, M. C.; Davidson, N.; Lester, H. A.; Kanner, B. I. (Science, 1990)

(untitled) - Bennett, E. R.; Kanner, B. I. (J. Biol. Chem., 1997)

(untitled) - Cai, G.; Salonikidis, P. S.; Fei, J.; Schwarz, W.; Schülein, R.; Reutter, W.; Fan, H. (FEBS J., 2005)

(untitled) - Hu, J.; Fei, J.; Reutter, W.; Fan, H. (Glycobiology, 2011)

(untitled) - Yamashita, A.; Singh, S. K.; Kawate, T.; Jin, Y.; Gouaux, E. (Nature, 2005)

(untitled) - Radian, R.; Kanner, B. I. (Biochemistry, 1983)

(untitled) - Zomot, E.; Bendahan, A.; Quick, M.; Zhao, Y.; Javitch, J. A.; Kanner, B. I. (Nature, 2007)

(untitled) - Forrest, L. R.; Tavoulari, S.; Zhang, Y.-W.; Rudnick, G.; Honig, B. (Proc. Natl. Acad. Sci. U. S. A., 2007)

(untitled) - Faham, S.; Watanabe, A.; Besserer, G. M.; Cascio, D.; Specht, A.; Hirayama, B. A.; Wright, E. M.; Abramson, J. (Science, 2008)

(untitled) - Weyand, S.; Shimamura, T.; Yajima, S.; Suzuki, S.; Mirza, O.; Krusong, K.; Carpenter, E. P.; Rutherford, N. G.; Hadden, J. M.; O'Reilly, J.; Ma, P.; Saidijam, M.; et al. (Science, 2008)

(untitled) - Abramson, J.; Wright, E. M. (Curr. Opin. Struct. Biol., 2009)

(untitled) - Ressl, S.; Terwisscha van Scheltinga, A. C.; Vonrhein, C.; Ott, V.; Ziegler, C. (Nature, 2009)

(untitled) - Möhler, H. (J. Recept. Signal Transduction, 2006)

(untitled) - Cope, D. W.; Di Giovanni, G.; Fyson, S. J.; Orbán, G.; Errington, A. C.; Lőrincz, M. L.; Gould, T. M.; Carter, D. A.; Crunelli, V. (Nat. Med., 2009)

(untitled) - Krystal, J. H.; Sanacora, G.; Blumberg, H.; Anand, A.; Charney, D. S.; Marek, G.; Epperson, C. N.; Goddard, A.; Mason, G. F. (Mol. Psychiatry, 2002)

(untitled) - Garcia-Alloza, M.; Tsang, S. W.; Gil-Bea, F. J.; Francis, P. T.; Lai, M. K.; Marcos, B.; Chen, C. P.; Ramirez, M. J. (Neurobiol. Aging, 2006)

(untitled) - Bröer, S. (Neurochem. Int., 2006)

(untitled) - Madsen, K. K.; Clausen, R. P.; Larsson, O. M.; Krogsgaard-Larsen, P.; Schousboe, A.; White, H. S. (J. Neurochem., 2009)

(untitled) - Chiu, C. S.; Jensen, K.; Sokolova, I.; Wang, D.; Li, M.; Deshpande, P.; Davidson, N.; Mody, I.; Quick, M. W.; Quake, S. R.; Lester, H. A. (J. Neurosci., 2002)

(untitled) - Ormö, M.; Cubitt, A. B.; Kallio, K.; Gross, L. A.; Tsien, R. Y.; Remington, S. J. (Science, 1996)

(untitled) - Yang, F.; Moss, L. G.; Phillips, G. N., Jr (Nat. Biotechnol., 1996)

(untitled) - van Oers, M. M.; Pijlman, G. P.; Vlak, J. M. (J. Gen. Virol., 2015)

(untitled) - Contreras-Gómez, A.; Sánchez-Mirón, A.; García-Camacho, F.; Molina-Grima, E.; Chisti, Y. (Biotechnol. Prog., 2014)

(untitled) - Lipfert, J.; Columbus, L.; Chu, V. B.; Lesley, S. A.; Doniach, S. (J. Phys. Chem. B, 2007)

(untitled) - Gonzales, A. L.; Lee, W.; Spencer, S. R.; Oropeza, R. A.; Chapman, J. V.; Ku, J. Y.; Eskandari, S. (J. Membr. Biol., 2007)

(untitled) - Soragna, A.; Bossi, E.; Giovannardi, S.; Pisani, R.; Peres, A. (Cell. Mol. Life Sci., 2005)

(untitled) - Perkins, D. N.; Pappin, D. J. C.; Creasy, D. M.; Cottrell, J. S. (Electrophoresis, 1999)

(untitled) - Ludwig, K.; Yan, S.; Fan, H.; Reutter, W.; Böttcher, C. (Biochem. Biophys. Res. Commun., 2003)